GMO approvals under pressure: How climate shocks shape policy across nations - Xiangwen Kong (PLoS ONE, 2025)
While GMO cultivation is often viewed as a strategy to buffer agriculture against climate change, its regulation remains controversial across countries. This study explores how climate shocks influence global patterns of genetically modified organism (GMO) approval. We develop a theoretical model and predict that climate shocks reduce the likelihood of GMO approvals in countries lacking a comparative advantage in GMO production. To test this, a local projection method is used to estimate the cumulative effects of climate shocks on approval activity. The results show that climate shocks tend to delay approvals, especially in countries with low GMO development capacity. These findings suggest that climate change may amplify regulatory inertia and intensify global policy divides on GMOs, raising concerns about the adaptability of global food systems under increasing environmental stress.